New trihydroxybriarane diterpenoids from an octocoral Briareum sp. (February 2020) - Hu, Chiung-Chin; Lin, Nai-Cheng; Peng, Bo-Rong; Chen, You-Ying; Wen, Zhi-Hong; Chang, Yu-Chia; Lee, Gene-Hsiang; Wu, Yang-Chang; Sung, Ping-Jyun
Graphical abstract: Highlights: New briaranes were obtained from octocoral Briareum sp. Structures of new briaranes were elucidated by spectroscopic methods. Briaranes showed anti-inflmmatory activity. Abstract: Chemical investigation of the extract from the supercritical CO2 extraction of an octocoral identified as Briareum sp., afforded a known briarane-type diterpenoid, excavatolide B (1 ), and a pair of new briaranes, briaviolides Y (2 ) and Z (3 ). The absolute configuration of 1 was determined by a single-crystal diffraction analysis and the structures of briaranes 2 and 3 were elucidated by using spectroscopic methods. Additionally, anti-inflammatory analysis showed that briarane 3 suppressed the iNOS and COX-2 levels, in LPS-stimulated RAW264.7 cells.